2023
DOI: 10.1101/2023.10.22.563498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Roles of RNAs in Chromatin Architecture Using Deep Learning

Shuzhen Kuang,
Katherine S. Pollard

Abstract: Recent studies have highlighted the impact of both transcription and transcripts on 3D genome organization, particularly its dynamics. Here, we propose a deep learning framework, called AkitaR, that leverages both genome sequences and genome-wide RNA-DNA interactions to investigate the roles of chromatin-associated RNAs (caRNAs) on genome folding in HFFc6 cells. In order to disentangle the cis- and trans-regulatory roles of caRNAs, we compared models with nascent transcripts, trans-located caRNAs, open chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…This value is relevant because when a variant is too close to the chromosome arm end– meaning near centromeres or telomeres– it will be positioned near the edge of the sequence ( Supplementary Fig. S1B ), which can have worse prediction accuracy than the rest of the sequence ( Kuang and Pollard 2023 ). Thus, SuPreMo is a flexible tool for performing ISM that can be applied across sequence-based ML models.…”
Section: Tool Descriptionmentioning
confidence: 99%
“…This value is relevant because when a variant is too close to the chromosome arm end– meaning near centromeres or telomeres– it will be positioned near the edge of the sequence ( Supplementary Fig. S1B ), which can have worse prediction accuracy than the rest of the sequence ( Kuang and Pollard 2023 ). Thus, SuPreMo is a flexible tool for performing ISM that can be applied across sequence-based ML models.…”
Section: Tool Descriptionmentioning
confidence: 99%
“…Recent studies have mapped RNA:DNA contacts at a global scale and have demonstrated that the majority of contacts occur locally to the RNA transcription, suggesting a mechanism for cis-regulation of genes by 'biochemical' contact of a lncRNA transcript (51)(52)(53). To examine this further, we evaluated the overlap of functional lncRNA-target relationships (defined by LOF experiments) and biochemical relationships (defined by RNA:DNA contacts).…”
Section: Cis-lncrna Transcripts Are Biochemically Bound To Their Targ...mentioning
confidence: 99%